Politicization of Water: Is Water Marketization a Solution for Ground Water Issue in Semarang? - Andaneswari, Annisa Kirana; Savirani, Amalinda (Unnes Political Science Journal, 2023)
This study intends to provide light on the subject of groundwater governance in Semarang City, Central Java, Indonesia. This article has sought to address two questions ; Questioning he provision of water among local government and also questioning whether water marketization is one of the fittest solution for ground water issues or an instrument to serve certain interest ?. The politicization of water refers to the ways in which issues related to water resources, access, management, and distribution become intertwined with political agendas, power struggles, and decision-making processes. Water marketization and politicization are two important and interconnected concepts related to the management and governance of water resources. The main finding of this research is that water marketization is being projected as the main remedy for ground water or land subsidence issue. The provision of water as a commodity is one of the political agenda that is framed through ground water issues at Semarang. While, local government keep pursuing this agenda, this research found out that water marketization is just oversimplified solution for ground water issue at Semarang.